Two Deoxythymidine Triphosphate Synthesis-Related Genes Regulate Obligate Symbiont Density and Reproduction in the Whitefly Bemisia tabaci MED - Yang, Zezhong; Gong, Cheng; Hu, Yuan; Zhong, Jie; Xia, Jixing; Xie, Wen; Yang, Xin; Guo, Zhaojiang; Wang, Shaoli; Wu, Qingjun; Zhang, Youjun (Frontiers in Physiology, 2021)
Deoxythymidine triphosphate (dTTP) is essential for DNA synthesis and cellular growth in all organisms. Here, genetic capacity analysis of the pyrimidine pathway in insects and their symbionts revealed that dTTP is a kind of metabolic input in several host insect/obligate symbiont symbiosis systems, including Bemisia tabaci MED/Candidatus Portiera aleyrodidarum (hereafter Portiera). As such, the roles of dTTP on both sides of the symbiosis system were investigated in B. tabaci MED/Portiera. Dietary RNA interference (RNAi) showed that suppressing dTTP production significantly reduced the density of Portiera, significantly repressed the expression levels of horizontally transferred essential amino acid (EAA) synthesis-related genes, and significantly decreased the reproduction of B. tabaci MED adults as well as the hatchability of their offspring. Our results revealed the regulatory role of dTTP in B. tabaci MED/Portiera and showed that dTTP synthesis-related genes could be potential targets for controlling B. tabaci as well as other sucking pests.